A tin-chlorine co-doped cupric oxide-based catalyst, a preparation method and application thereof
Patent Information
- Application Number
- CN202611197535.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-07
- Publication Date
- 2026-10-27
AI Technical Summary
[0007]本发明的目的在于解决现有技术中CuO基催化剂掺杂均匀性差、阴阳离子掺杂需分步进行、工艺复杂等问题,提供一种锡氯双掺杂氧化铜基催化剂及其制备方法与应用,通过共沉淀法及热处理,对CuO晶格进行原位Cl-阴离子掺杂,并结合Sn4+阳离子掺杂,获得阴阳离子共掺杂的CuO基催化剂,在提高CuO催化活性的同时降低生产成本,有利于实现工业化生产
(1)本发明提供的锡氯双掺杂氧化铜基催化剂,为一种全新的多元素掺杂氧化铜基催化剂,不仅结晶性良好、晶粒尺寸分布均匀,而且具有优异的催化活性,相比于单一掺杂的氧化铜,其催化效率显著提升。尤其是在电催化体系中,表现出更好的单一选择性。
Smart Images

Figure CN122974341A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of inorganic functional catalytic materials technology, specifically relating to a tin-chlorine dual-doped copper oxide-based catalyst, its preparation method, and its application. Background Technology
[0002] Copper oxide (CuO), as an important p-type semiconductor material, has broad application prospects in heterogeneous catalysis, photocatalysis, gas sensing, and electrochemical energy storage due to its unique electronic structure, good chemical stability, and abundant reserves. In the field of catalysis, CuO and its composite materials have been extensively studied for heterogeneous Fenton reactions. Its advantage lies in its ability to achieve efficient degradation of organic pollutants over a wide pH range (3-10), thus overcoming the limitation of the traditional homogeneous Fenton system (Fe2+ / H2O2) which can only operate under acidic conditions of pH 2.5-3.5.
[0003] When pure CuO is used to activate H2O2, it exhibits limited intrinsic catalytic activity; Cu + The slow regeneration rate, severe electron-hole recombination, high copper ion dissolution during recycling, and significant degradation efficiency decay under neutral conditions are drawbacks that restrict the practical engineering application of CuO. In recent years, controlling the electronic structure and surface properties of CuO through heteroelement doping has become an important strategy for improving its catalytic performance. By introducing heteroatoms into the CuO lattice, the electronic structure can be controlled, oxygen vacancies can be constructed, and redox cycling ability can be improved, thereby enhancing the catalyst's ability to activate H₂O₂.
[0004] In existing CuO doping modification patents and literature, most schemes only achieve single-element doping. For example, some studies have disclosed chlorine (Cl) modified CuO catalysts, introducing chlorine into the CuO lattice to replace some oxygen sites, which can adjust the surface acidity of the catalyst, optimize the band structure, increase the oxygen vacancy content, and improve catalytic degradation performance. However, in single-Cl doping systems, chlorine components are easily lost during the reaction process, the lattice structure is easily destroyed, and the catalytic system has insufficient anti-interference ability.
[0005] In addition, the existing methods for preparing CuO-based catalytic materials also have the following problems: (1) poor uniformity of heterogeneous element doping, and the traditional solid-state sintering or impregnation method has problems such as agglomeration of dopant elements and difficulty in entering the crystal lattice; (2) anion doping (such as Cl) - (3) Doping usually requires the introduction of additional doping sources or post-processing steps, making the process complex; (4) Cation doping and anion doping are usually carried out in steps, making it difficult to achieve simultaneous doping in one step; (5) There is a lack of simplified process routes to achieve simultaneous anion and cation doping with a single precursor.
[0006] Therefore, developing a multi-element co-doped CuO-based catalyst and its preparation method, improving the catalyst's catalytic activity under a wide pH range, and simplifying the industrial preparation process are of great practical significance for promoting the practical application of copper-based heterogeneous Fenton catalysts. Summary of the Invention
[0007] The purpose of this invention is to solve the problems of poor doping uniformity, the need for step-by-step doping of anions and cations, and complex processes in existing CuO-based catalysts. It provides a tin-chlorine dual-doped copper oxide-based catalyst, its preparation method, and its application. Through co-precipitation and heat treatment, in-situ Cl-doping of the CuO lattice is achieved. - Anion doping, combined with Sn 4+ Cation doping yields CuO-based catalysts co-doped with anions and cations, which improves the catalytic activity of CuO while reducing production costs, thus facilitating industrial production.
[0008] To achieve the above objectives, on the one hand, the present invention provides a tin-chlorine dual-doped copper oxide-based catalyst, which is a Sn and Cl dual-doped CuO catalyst, wherein the Sn content in the catalyst is 0.05~5% based on the Sn / Cu molar ratio, and the Cl content in the catalyst is 1~10% based on the Cl / O molar ratio.
[0009] Preferably, in the above-mentioned tin-chlorine dual-doped copper oxide-based catalyst, the Sn content in the catalyst is 0.05~2% based on the Sn / Cu molar ratio, and the Cl content in the catalyst is 1~5% based on the Cl / O molar ratio.
[0010] On the other hand, the present invention also provides a method for preparing a tin-chlorine dual-doped copper oxide-based catalyst, comprising the following steps: S1. Preparation of precursors: At room temperature, CuCl2·2H2O and SnCl4·5H2O are completely dissolved in deionized water to form a homogeneous mixed salt solution. Under stirring, NaOH solution is slowly added to the mixed salt solution, controlling the reaction pH at 7-11, so that Cu... 2+ Sn 4+ With Cl - OH - They co-precipitate to form a Sn-doped basic copper chloride precursor solution; The amount of CuCl2·2H2O and SnCl4·5H2O added is 0.5%~5% based on the Sn / Cu molar ratio; S2. Precursor heat treatment: After the obtained precursor solution is stirred and mixed evenly, it is subjected to static aging, washing and vacuum drying to obtain precursor powder; the obtained precursor powder is kept at 250-550℃ for 1-6 hours in air atmosphere to obtain tin-chlorine double-doped copper oxide-based catalyst.
[0011] The method for preparing a tin-chlorine dual-doped copper oxide-based catalyst provided by this invention uses CuCl2·2H2O as the copper source and chlorine source, SnCl4·5H2O as the tin source and auxiliary chlorine source, and NaOH as the precipitant. It employs a room-temperature co-precipitation method, controlling the amount of NaOH added and the reaction pH to achieve the desired Cu... 2+ With Cl - Co-precipitation forms a basic copper chloride (Cu2(OH)3Cl) precursor, while simultaneously achieving Sn... 4+ In-situ doping followed by low-temperature heat treatment transforms the precursor into a Sn / Cl co-doped CuO catalyst. The specific preparation principle is as follows: (1) Coprecipitation principle: In alkaline medium, Cu 2+ With OH - Combined to form a sparingly soluble hydroxide precipitate, while Cl - Through with Cu 2+ The coordination effect causes it to co-precipitate into the solid phase, forming the basic copper chloride Cu2(OH)3Cl precursor. 4+ Under alkaline conditions, hydrolysis produces tin hydroxide / oxychloride, which precipitates simultaneously with the Cu-based precursor, causing Sn to... 4+ It exhibits atomic-level uniform dispersion in the solid phase.
[0012] (2) Principle of in-situ anion doping: During the thermal decomposition of Cu2(OH)3Cl precursor into CuO, Cl in its crystal structure - Not all of them escaped; some Cl... - O sites retained in the CuO lattice form CuO 1-x Cl x Solid solution structure to achieve Cl - In-situ doping of anions. Compared with the traditional external chlorine source doping method, the Cl of this invention... - Derived from the precursor itself, no additional dopant is needed, simplifying the process and improving doping uniformity.
[0013] (3) Cation doping principle: Sn is pre-uniformly dispersed in the precursor 4+ During thermal decomposition, cation sites that enter the CuO lattice (partially replacing Cu) 2+ ), to achieve Sn 4+ Cation doping.
[0014] (4) The principle of synergistic effect of dual doping: Sn 4+ Cation doping and Cl - Anion doping occurs simultaneously, and the two processes synergistically regulate the electronic structure and band structure of CuO. 4+ The introduction of Cl can increase carrier concentration and improve conductivity. -By introducing an adjustable bandgap and enhancing the response, the dual-doping effect can produce catalytic performance superior to that of single-doping.
[0015] (5) Temperature control principle: Low-temperature heat treatment can achieve the complete conversion of Cu2(OH)3Cl precursor to CuO, while avoiding Sn segregation or Cl segregation caused by excessively high temperatures. - Excessive volatilization ensures the maximization of the dual-doping effect.
[0016] In the preparation method of the above-mentioned tin-chlorine dual-doped copper oxide-based catalyst, in step S1, NaOH solution is added to maintain the pH of the reaction system in the range of 7-11 to control the amount of NaOH added. When the pH exceeds 11 and the reaction endpoint is reached, the addition of NaOH solution is stopped, the reaction ends and proceeds to step S2.
[0017] In the preparation method of the above-mentioned tin-chlorine dual-doped copper oxide-based catalyst, in step S1, CuCl2·2H2O is used as the copper source and chlorine source, SnCl4·5H2O is used as the tin source and auxiliary chlorine source, and NaOH is used as the precipitant. No other auxiliary agents or additional doping sources are required. The Sn-doped basic copper chloride (Cu2(OH)3Cl) precursor can be prepared in one step via co-precipitation. Preferably, the concentration of CuCl2·2H2O is 0.1~0.5 mol / L, and the concentration of NaOH solution is 0.5~2 mol / L.
[0018] In the preparation method of the above-mentioned tin-chlorine dual-doped copper oxide-based catalyst, in step S1, NaOH precipitant is slowly added to the mixed salt solution while continuously stirring, the purpose of which is to control the OH content of the system. - Release rate, avoid excessively high local alkali concentration, promote Cu 2+ Sn 4+ To maximize the synchronous precipitation of hydroxides and improve the uniformity of the precipitation, the precursor nucleation rate is controlled to suppress hard agglomeration of particles, improve the mixing uniformity of each component, and facilitate the effective embedding of chlorine into the hydroxide precursor. This lays the foundation for subsequent calcination to obtain a uniformly co-doped CuO catalyst with Sn and Cl. In this invention, the NaOH solution can be added dropwise or slowly, with the addition time preferably being 0.5~4 hours.
[0019] In the preparation method of the above-mentioned tin-chlorine dual-doped copper oxide-based catalyst, step S2, the static aging process allows the newly formed hydroxide microcrystals to dissolve and recrystallize, improving the precursor grain structure; promoting further diffusion and rearrangement of copper and tin ions within the solid phase; and simultaneously releasing free sodium and chloride ions encapsulated within the precipitate aggregates, facilitating subsequent water washing to remove amorphous adsorbed impurity ions, distinguishing between lattice-doped chloride and free impurity chloride, and improving the precursor particle state. The precursor solution is allowed to stand at room temperature (referring to the ambient indoor temperature, which has little impact on the product regardless of the season) until a solid-liquid mixture with a clear upper layer and a precipitated lower layer is obtained. The standing time is preferably not less than 5 hours.
[0020] Further, the precursor solution after standing and aging is centrifuged to obtain a precipitate. The precipitate is repeatedly washed with ethanol and deionized water, and then placed in a vacuum oven and dried at 60-80°C for 6-12 hours to obtain a precursor powder.
[0021] In the above method for preparing tin-chlorine dual-doped copper oxide-based catalysts, in step S2, the precursor Cu2(OH)3Cl undergoes thermal decomposition, and the Cl it carries... - Some of the Cl is retained in the CuO lattice, occupying O sites, thus achieving in-situ Cl. - Anion doping; simultaneously, Sn pre-doped in the precursor 4+ During thermal decomposition, cation sites enter the CuO lattice, realizing Sn 4+ Cation doping. Simultaneous dual doping of anions and cations is achieved in one step through thermal conversion of a single precursor.
[0022] Too low a heat treatment temperature will lead to incomplete decomposition of the precursors. The hydroxide precursors (Cu(OH)2, Sn(OH)4) cannot be completely decomposed and transformed into the CuO crystalline phase, resulting in insufficient crystallinity. At the same time, Sn... 4+ Cl - It is difficult for Sn to enter CuO lattice sites, resulting in poor doping effect; while excessively high temperatures can cause changes in the valence state of Sn or Cl. - Excessive volatilization destroys the dual-doped structure. The heat treatment temperature of this invention is 250–550°C. At this temperature, the precursor can fully decompose to form the CuO main crystalline phase, allowing the Cl carried by the precursor to be released. - Partially retained in the CuO lattice to achieve anion doping; simultaneously, the atoms possess moderate diffusion capability, Sn 4+ Successful doping into the CuO lattice cation sites achieves cation doping; grains do not grow excessively, maintaining a high specific surface area, thus achieving Sn-Cl synergistic modification. Preferably, the heat treatment temperature is 400–450 °C, and the heating rate is 1–5 °C·min. -1Furthermore, the heat treatment temperature is 400℃, and the heating rate is 1°C·min. -1 The heat treatment time is 1 hour.
[0023] Furthermore, the present invention also provides an application of the above-mentioned tin-chlorine dual-doped copper oxide-based catalyst in heterogeneous Fenton catalysis or photocatalytic degradation of organic pollutants.
[0024] The tin-chlorine dual-doped copper oxide-based catalyst, its preparation method, and its application provided by this invention have the following beneficial effects: (1) The tin-chlorine dual-doped copper oxide-based catalyst provided by the present invention is a novel multi-element doped copper oxide-based catalyst. It not only has good crystallinity and uniform grain size distribution, but also has excellent catalytic activity. Compared with single-doped copper oxide, its catalytic efficiency is significantly improved. In particular, it exhibits better single selectivity in electrocatalytic systems.
[0025] (2) The tin-chlorine dual-doped copper oxide-based catalyst provided by the present invention is prepared by room temperature co-precipitation method-low temperature heat treatment using CuCl2·2H2O as copper source and chlorine source, SnCl4·5H2O as tin source and auxiliary chlorine source, and NaOH as precipitant. It achieves efficient doping of tin and chlorine, with fewer preparation steps, lower difficulty and shorter cycle. It does not require extra auxiliary reagents and has no toxic or harmful reagents. The reaction conditions are mild and do not require strict control. The equipment requirements are low, which is conducive to industrial production and ensures the safety and environmental protection of production.
[0026] (3) The tin-chlorine dual-doped copper oxide-based catalyst provided by the present invention has adjustable catalytic performance. By adjusting the amount of SnCl4 added and the reaction pH value, the Sn doping amount and Cl doping amount can be independently controlled, providing a flexible control method for optimizing catalytic performance.
[0027] (4) The preparation method of the tin-chlorine dual-doped copper oxide-based catalyst provided by the present invention, Sn 4+ Atomic-level uniform dispersion is achieved in the precursor stage through co-precipitation, avoiding the problem of dopant element agglomeration in traditional impregnation or solid-phase methods; Cl - Originating from the precursor itself, tin and chlorine doping is uniformly distributed in the crystal lattice, resulting in good uniformity of tin and chlorine doping.
[0028] (5) The method for preparing the tin-chlorine dual-doped copper oxide-based catalyst provided by the present invention utilizes the characteristic that the Cu2(OH)3Cl precursor is converted into CuO in situ during heat treatment, so that the Cl carried by the precursor itself can be converted into CuO. - Partially retained in the CuO lattice for anion doping, while Sn pre-doped in the precursor 4+Cation doping is achieved by entering cation sites. Both cation and anion doping are completed in a single heat treatment step, greatly simplifying the process.
[0029] (6) The tin-chlorine dual-doped copper oxide-based catalyst provided by the present invention can be widely used in many fields such as heterogeneous Fenton catalytic degradation of organic pollutants, photocatalytic water splitting, gas sensing and electrochemical energy storage, and has good application prospects. Attached Figure Description
[0030] Figure 1 These are X-ray diffraction patterns of the Sn / Cl double-doped CuO sample prepared in Example 1, and the CuO and Cl-doped CuO samples prepared in Comparative Examples 1-2, respectively. Figure 2 This is an electron microscope image of the Sn / Cl double-doped CuO sample prepared in Example 1; Figure 3 This is an electron microscope image of the CuO sample prepared in Comparative Example 1; Figure 4 This is an electron microscope image of the Cl-doped CuO sample prepared in Comparative Example 2; Figure 5 The diagram shows the catalytic performance of the double-doped CuO prepared in Example 1 and the Cl-doped CuO and CuO prepared in Comparative Examples 1-2, respectively. Detailed Implementation
[0031] The technical solutions of various embodiments of the present invention will be clearly and completely described in conjunction with the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are part of the present invention.
[0032] Example 1
[0033] The tin-chlorine dual-doped copper oxide-based catalyst provided in this embodiment is prepared by the following steps: S1. Preparation of the precursor: At room temperature (approximately 25°C), dissolve 10 mmol CuCl₂·2H₂O and 0.05 mmol SnCl₄·5H₂O in 100 ml of deionized water (Sn / Cu molar ratio = 0.5%), and stir until completely dissolved to obtain a homogeneous mixed salt solution. Under continuous stirring, slowly add 1 M NaOH solution dropwise to the mixed salt solution, controlling the rate of alkali addition to gradually increase the pH of the reaction system and maintain it between 7 and 9. After the addition is complete, a Sn-doped basic copper chloride precursor solution is formed.
[0034] S2. Precursor Heat Treatment: After stirring the obtained precursor solution for another 30 minutes to achieve homogeneity, allow it to stand at room temperature for 5 hours to obtain a solid-liquid mixture with a clear upper layer and a precipitated lower layer. Centrifuge the lower precipitate and wash it repeatedly with deionized water (3 times) and anhydrous ethanol (2 times). Place the washed precipitate in a vacuum oven and dry it overnight at 60°C to obtain precursor powder. Place the obtained precursor powder in a tube furnace and heat it in air at 1°C·min. -1 The heating rate was increased to 400°C, held for 1 hour, and then cooled to room temperature in the furnace to obtain a Sn and Cl co-doped CuO catalyst. The Sn content in the catalyst was 0.05% based on the Sn / Cu molar ratio, and the Cl content in the catalyst was 1% based on the Cl / O molar ratio.
[0035] Examples 2-4 Compared with Example 1, Examples 2-4 differ only in the standing time in step S2; all other experimental conditions and parameters remain unchanged. The standing times for Examples 2-4 were 6 hours, 8 hours, and 12 hours, respectively. The phase composition of the products obtained in Examples 2-4 was consistent with that of Example 1, indicating that a standing time of at least 5 hours yields good products.
[0036] Examples 5-7 Compared with Example 1, Examples 5-7 differ only in the heat treatment temperature in step S2; all other experimental conditions and parameters remain unchanged. The heat treatment temperatures for Examples 5-7 were 350°C, 450°C, and 500°C, respectively.
[0037] Examples 8-10 Compared with Example 1, Examples 8-10 differ only in the amount of CuCl2·2H2O and SnCl4·5H2O used in step S1; all other experimental conditions and parameters remain unchanged. In Examples 8-10, the amounts of CuCl2·2H2O and SnCl4·5H2O added, based on the Sn / Cu molar ratio, are 1%, 2%, and 5%, respectively. The final Sn / Cl co-doped CuO catalyst is obtained. In Example 8, the Sn content in the catalyst is 1% based on the Sn / Cu molar ratio, and the Cl content is 3% based on the Cl / O molar ratio. In Example 9, the Sn content in the catalyst is 2% based on the Sn / Cu molar ratio, and the Cl content is 5% based on the Cl / O molar ratio. In Example 10, the Sn content in the catalyst is 5% based on the Sn / Cu molar ratio, and the Cl content is 10% based on the Cl / O molar ratio.
[0038] Comparative Example 1 This comparative example will prepare a CuO control sample, and the preparation method includes the following steps: At room temperature (approximately 25°C), dissolve 10 mmol of CuCl₂·2H₂O in 100 mL of deionized water and stir until completely dissolved. While continuously stirring, slowly add 1 M NaOH solution dropwise to the above solution, controlling the rate of alkali addition to maintain the pH of the reaction system between 10 and 11 (increasing the amount of NaOH ensures sufficient Cl₂ concentration). - (The residue was thoroughly washed away). After the addition was complete, stirring continued for 30 minutes, and the mixture was allowed to stand at room temperature for 5 hours. Subsequent washing, drying, and heat treatment steps were exactly the same as in Example 1, ultimately yielding an undoped CuO control sample.
[0039] Comparative Example 2 This comparative example serves as a control experiment for the embodiments. A control sample of CuO doped only with Cl was prepared. The preparation method includes the following steps: At room temperature (approximately 25°C), dissolve 10 mmol of CuCl₂·2H₂O in 100 mL of deionized water and stir until completely dissolved. While continuously stirring, slowly add 1 M NaOH solution dropwise to the above solution, controlling the rate of alkali addition to maintain the pH of the reaction system between 7 and 9 (consistent with Example 1, ensuring that Cl₂ is dissolved in water). - (Some remains in the precursor). After the addition is complete, continue stirring for 30 minutes, and then let the mixture stand at room temperature for 5 hours. Subsequent washing, drying, and heat treatment steps are exactly the same as in Example 1, finally yielding a Cl-doped CuO sample (without Sn). This comparative example is used to verify the individual contribution of Sn doping.
[0040] Comparative Example 3 This comparative example serves as a control experiment for the embodiment. A control sample of CuO doped only with Sn was prepared. The preparation method includes the following steps: At room temperature (approximately 25°C), 10 mmol of Cu(NO3)2·3H2O (using copper nitrate instead of copper chloride to eliminate Cl) is added. - Dissolve 0.05 mmol of SnCl₄·5H₂O in 100 mL of deionized water and stir until completely dissolved. While continuously stirring, slowly add 1 M NaOH solution dropwise to the above solution, controlling the reaction pH to 7–9. Subsequent operations are the same as in Example 1, ultimately obtaining a Sn-doped CuO sample (without Cl). This comparative example is used to verify the individual contribution of Cl doping.
[0041] like Figure 1The figure shows the X-ray diffraction patterns of Sn / Cl double-doped CuO prepared in Example 1, and Cl-doped CuO and CuO prepared in Comparative Examples 1-2, respectively. As can be seen from the figure, the positions of the main diffraction peaks of the three samples all match those of the CuO standard card PDF#74-1021, indicating that after doping with Cl and simultaneously doping with Sn / Cl, the sample materials still maintain the main crystal structure of CuO. No Sn-related impurity peaks were observed in the spectra, indicating that Sn does not exist in large quantities as an independent crystalline compound.
[0042] like Figure 2-4 As shown, Figure 2 This is an electron micrograph of the Sn / Cl double-doped CuO prepared in Example 1. Figure 3 This is an electron microscope image of the CuO prepared in Comparative Example 1. Figure 4 The image shows an electron microscope (EM) image of Cl-doped CuO prepared in Comparative Example 2. As can be seen from the image, with the introduction of Cl and Sn-Cl, the particles gradually become smaller and more uniform, indicating the presence of the introduced material.
[0043] like Figure 5 The figure shows the catalytic performance of the double-doped CuO prepared in Example 1 and the Cl-doped CuO and CuO prepared in Comparative Examples 1-2, respectively. When these were prepared as electrodes and applied in an electrocatalytic CO2 reduction system, the methane Faradaic efficiency of Cl-doped CuO was observed to be significantly higher than that of CuO. Comparison shows that the methane Faradaic efficiency of the Sn-Cl double-doped CuO catalyst is higher than that of single-doped and undoped catalysts within the test voltage range. This indicates that Sn-Cl double-doped CuO has better catalytic performance than Cl-doped CuO and CuO in the catalytic field.
[0044] Those skilled in the art will recognize that the embodiments described herein are intended to help the reader understand the principles of the invention, and should be understood that the scope of protection of the invention is not limited to such specific statements and embodiments. Those skilled in the art can make various other specific modifications and combinations based on the technical teachings disclosed in this invention without departing from the spirit of the invention, and these modifications and combinations are still within the scope of protection of this invention.
Claims
1. A tin-chlorine dual-doped copper oxide-based catalyst, characterized in that: The catalyst is a Sn and Cl co-doped CuO catalyst, wherein the Sn content in the catalyst is 0.05~5% based on the Sn / Cu molar ratio, and the Cl content in the catalyst is 1~10% based on the Cl / O molar ratio.
2. The tin-chlorine dual-doped copper oxide-based catalyst according to claim 1, characterized in that: The Sn content in the catalyst is 0.05-2% based on the Sn / Cu molar ratio, and the Cl content in the catalyst is 1-5% based on the Cl / O molar ratio.
3. A method for preparing a tin-chlorine dual-doped copper oxide-based catalyst according to claim 1 or 2, characterized in that: Includes the following steps: S1. Preparation of precursors: At room temperature, CuCl2·2H2O and SnCl4·5H2O are completely dissolved in deionized water to form a homogeneous mixed salt solution. Under stirring, NaOH solution is slowly added to the mixed salt solution, controlling the reaction pH at 7-11, so that Cu... 2+ Sn 4+ With Cl - OH - They co-precipitate to form a Sn-doped basic copper chloride precursor solution; The amount of CuCl2·2H2O and SnCl4·5H2O added is 0.05%~5% based on the Sn / Cu molar ratio; S2. Precursor heat treatment: After the obtained precursor solution is stirred and mixed evenly, it is subjected to static aging, washing and vacuum drying to obtain precursor powder; the obtained precursor powder is kept at 250-550℃ for 1-6 hours in air atmosphere to obtain tin-chlorine double-doped copper oxide-based catalyst.
4. The method for preparing the tin-chlorine dual-doped copper oxide-based catalyst according to claim 3, characterized in that: In step S1, the concentration of CuCl2·2H2O is 0.1~0.5 mol / L, and the concentration of NaOH solution is 0.5~2 mol / L.
5. The method for preparing the tin-chlorine dual-doped copper oxide-based catalyst according to claim 3, characterized in that: In step S1, the NaOH solution is added drop by drop or slowly, and the addition time is 0.5 to 4 hours.
6. The method for preparing the tin-chlorine dual-doped copper oxide-based catalyst according to claim 3, characterized in that: In step S2, the heat treatment temperature is 400~450℃, and the heating rate is 1~5°C·min. -1 .
7. The method for preparing the tin-chlorine dual-doped copper oxide-based catalyst according to any one of claims 3-6, characterized in that: In step S2, the precursor solution is left to stand at room temperature until a solid-liquid mixture with a clear upper layer and a precipitated lower layer is obtained.
8. The method for preparing the tin-chlorine dual-doped copper oxide-based catalyst according to any one of claims 3-6, characterized in that: The settling time should be no less than 5 hours.
9. The method for preparing the tin-chlorine dual-doped copper oxide-based catalyst according to any one of claims 3-6, characterized in that: In step S2, the precursor solution after standing is centrifuged to obtain a precipitate. The precipitate is washed repeatedly with ethanol and deionized water, and then placed in a vacuum oven and dried at 60-80℃ for 6-12 hours to obtain precursor powder.
10. The application of the tin-chlorine dual-doped copper oxide-based catalyst of claim 1 or 2 in heterogeneous Fenton catalysis or electrocatalysis.